The neurological basis of violence. - Delgado, José M. R. (International Social Science Journal, 1971)
The chronicle of human civilization is the story of a co-operative venture consistently marred by destructive acts and every advance has been accompanied by the increased efficiency of violent behaviour. The invention of explosives, development of firearms and modern means of transportation have made unskilled individuals more powerful than mythical warriors of the past, and have placed a vast arsenal of ingenious weapons at the disposal of man. Violence is displaced aggression which surfaces in response to frustration about environmental circumstances. Commonly cited causes include poverty, overpopulation, hunger, social injustice and ideological or racial antagonisms. Behaviour can also be evoked by brain stimulation which is not just a fragment of violence or a reaction to discomfort but is a complete and purposefully directed act. Violence is a pattern of behavioural response related to the function of specific areas of the brain. Expressions of violent responses depend essentially on previous sensory inputs and experience.